Dialogic Communication During Covid-19 Pandemic: An Analysis on Technoparks’ Social Media Usage in Turkey - Hediye Aydoğan (Connectist Istanbul University Journal of Communication Sciences)
With the outbreak of the Covid-19 pandemic, social media has promptly become an essential communication tool for institutions and organizations to generate and disseminate information as well as building effective dialogue with the public. In this regard, it was vital for technoparks like many other organizations to effectively manage their social media accounts in order to inform and communicate with their stakeholders. Therefore, the current study aims to investigate how technoparks in Turkey used their social media platforms (Facebook, Twitter, and Instagram) during the first three months of the Covid-19 pandemic to facilitate dialogic communication with stakeholders, and to present the quality index of technoparks in terms of dialogic communication in social media management. In line with this aim, a content analysis of social media profiles maintained by 70 active technoparks examines the use of dialogic features originally developed in Dialogic Communication Theory. Results indicate that technoparks could not fully utilize the dialogic features of the social media platforms and that they mostly preferred to manage their social media platforms to disseminate information, which means they were away from dialogue. Recommendations are made for future studies and practitioners in terms of dialogic communication in social media management.